A Powder Self‐Healable Hydrogel Electrolyte for Flexible Hybrid Supercapacitors with High Energy Density and Sustainability. Issue 10 (16th February 2021) - Huang, Hailong; Han, Lu; Fu, Xiaobin; Wang, Yanling; Yang, Zhongli; Pan, Likun; Xu, Min
Abstract: Ionic conductive hydrogel electrolyte is considered to be an ideal electrolyte candidate for flexible supercapacitor due to its flexibility and high conductivity. However, due to the lack of effective recycling methods, a large number of ineffective flexible hydrogel supercapacitors caused by some irreversible damages and dryness of hydrogel electrolyte are abandoned, which would induce heavy economic and environmental protection problems. Herein, a smart ionic conductive hydrogel (SPMA‐Zn: ZnSO4 /sodium alginate/polymethylacrylic acid) is developed for flexible hybrid supercapacitor (SPMA‐ZHS). The SPMA‐Zn exhibits an excellent self‐healing ability and can recover its electrochemical performance after multiple mechanical damages. More importantly, it possesses an outstanding powder self‐healable property, which could easily regenerate the hydrogel electrolyte after powdering, and maintain stable electrochemical performance of SPMA‐ZHS. Besides, the SPMA‐ZHS displays excellent electrochemical performance with a wide and stable working voltage range of 0–2.2 V, high energy density of 164.13 Wh kg −1 at the power density of 1283.44 Wh kg −1 and good stability with a capacity retention of 95.3% after 5000 charge/discharge cycles at 10 A g −1 . The strategy in this work would provide a new insight in exploring flexible hydrogel electrolyte‐based supercapacitor with good sustainability and high energy density for flexible wearable electronic devices. Abstract : A recyclable hydrogel electrolyte with excellent conductivity and self‐healing ability is designed for flexible supercapacitors. Compared with existing flexible supercapacitor, the sodium alginate polymethylacrylic acid hydrogels based zinc hybrid supercapacitor not only exhibits high energy density and excellent self‐healing ability, but also possesses good powder self‐healable ability to guarantee the hydrogel electrolyte‐based supercapacitor with excellent recyclability, exhibiting great potential for sustainable flexible energy storage devices.